مادة العربية وتطويرها ببرنامج التعلم التفاعلي لترقية قدرة الطلبة على مهارة الاستماع - azwir, azwir; Fajri, Ikramul; Furqan, Furqan (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2024)
This research addresses the listening problem students suffer from when studying listening skills. This problem is addressed by developing the listening material based on the interactive learning program as one of the modern educational methods. This development research is based on the ADDIE method, and the research population was all 489 students at Bab Al-Najah Institute. The sample is fourth-semester students, numbering 31 students. The result, after going through the required steps of conducting developmental research, indicated that the interactive learning program had an effective impact on improving students’ ability to listen since the result from the experts’ questionnaire was 84% and (the test) was greater than the result of the table (table) or 2.04 > 23. 66>2,75.